To simplify the given expression \( \sqrt[10]{x^{109}} \), we can apply the property of exponents.
The expression can be rewritten using exponent rules:
\[ \sqrt[10]{x^{109}} = x^{\frac{109}{10}} = x^{10.9} \]
Now let's see how this is represented among the given answer choices:
To match with the format provided in the options, let's express \( x^{10.9} \) more clearly.
-
Option A: \( x^{11} \sqrt[10]{x^{10}} \)
- Simplifying: \( x^{11} \cdot \sqrt[10]{x^{10}} = x^{11} \cdot x^{\frac{10}{10}} = x^{11} \cdot x^{1} = x^{12} \), which is incorrect.
-
Option B: \( x^{10} \sqrt[10]{x^{9}} \)
- Simplifying: \( x^{10} \cdot \sqrt[10]{x^{9}} = x^{10} \cdot x^{\frac{9}{10}} = x^{10 + 0.9} = x^{10.9} \), which matches.
-
Option C: \( x^{11x} \), which doesn't match.
-
Option D: \( x^{10x} \), which doesn't match.
Thus, the correct equivalent expression for \( \sqrt[10]{x^{109}} \) is:
Answer: \( x^{10} \sqrt[10]{x^{9}} \)